NUR AL-DIN AL-SHIRAZI AND HIS METHOD IN THE BOOK (AL-MISBAAH FI SHARAH TALKHEES AL-MUFTAH) - Oroba Hassan Jassim; Prof. Dr. Khalil Muhammad Saeed Mukhlif (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This research aims to identify a scientist from the eighth century A.H, He is Muhammad Ibn Abi Al-Tayyib Nur Al-Din Al-Shirazi. He was proficient in most of the Arabic sciences, as well as the sciences of philosophy and logic. And then getting acquainted with his rhetorical book (Al-Misbaah fi Sharah Talkhees Al-Muftah), in which he explained the book (Al- Talkhees fi Al-Ulum Al-Balagha) by Al-Khatib Al-Qazwini (D. 739 AH), This study shows the importance of the book and its great benefits for those who wish to delve into the science of rhetoric. The importance of this study lies in getting to know the method that Al-Shirazi took in explaining this book and the way he presented his scientific material.